Islamic Religious Education in Pesantren in Fostering Religious Moderation - Nabila Elvana; Muhammad Masduki (JIGC (Journal of Islamic Guidance and Counseling), 2022)
Indonesian society is a diverse cultural society with its plurality. Diversity includes differences in culture, religion, race, language, ethnicity, tradition and so on. In such a multicultural society, tensions and conflicts often occur between cultural groups and have an impact on the harmony of life. Therefore, this article aims to provide information about the impact of Islamic religious education on religious moderation in the scope of Islamic boarding schools and how to apply tolerance, respect, and fairness in society. The research approach was carried out qualitatively, where data collection was obtained by means of literature studies and questionnaires. The method used is library research. The conclusion of this article concludes that studies in multicultural life such as Indonesia require multicultural understanding and awareness that respects differences, pluralism and the willingness to interact with anyone fairly. Therefore, religious moderation is needed in the form of acknowledging the existence of other parties, being tolerant, respecting differences of opinion and not forcing one's will by force. In this regard, the role of the government, community leaders and religious instructors is very much needed to socialize and subvert religious moderation to the community for the realization of harmony and peace. Indonesian people in the Unitary State of the Republic of Indonesia have diversity, including various ethnicities, languages, religions, cultures, and social statuses. Diversity can be an "integrating force" that binds the community but can be the cause of clashes between cultures, races, ethnicities, religions and cultures. Awareness and understanding of cultural diversity (multicultural), especially religious diversity, is increasingly needed by the community. Religious counseling as a servant of the Suka community has the competence and carries out a moderation movement to increase the peace of the people of religious moderation to the community for the realization of harmony and peace.